Harry Snyder diary and Bible - Snyder, Harry, active 1863-1865.
Diary kept by Snyder during his Civil War service with the 17th Ohio Infantry Regiment and as a carpenter in Geneseo, Ill., following his discharge in 1864. Subjects include Snyder's participation in the Battle of Chickamauga, Georgia; and his service in military hospitals in Nashville and Chattanooga, Tenn. Also documents his work as a carpenter for the Chicago and Rock Island Railroad Company and others. Includes a Bible presented to Snyder upon his enlistment in 1861.
Union Army soldier and carpenter.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: United States. -- Army. -- Ohio Infantry Regiment, 17th (1861-1865); Chicago and Rock Island Railroad Company; Carpentry -- Illinois; Chickamauga, Battle of, Ga., 1863.; Railroads -- Illinois; Chattanooga (Tenn.) -- History -- Civil War, 1861-1865.; Geneseo (Ill.) -- History; Georgia -- History -- Civil War, 1861-1865.; Ohio -- History -- Civil War, 1861-1865.; Nashville (Tenn.) -- History -- Civil War, 1861-1865.; Tennessee -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Hospitals; United States -- History -- Civil War, 1861-1865 -- Medical care; Carpenters; Soldiers